Orientational Capability Analysis of a 2UPR-SPR Parallel Manipulator - Che Linxian; Zhang Rong; Zhang Caifang; Wang Taofen (Jixie chuandong)
The parallel module of Exechon machine tool is developed based on the 3 degree-of-freedom (DOF) 2UPR-SPR mechanism, which is a parallel spindle head with two rotational (orientational) DOFs and one translational DOF. The output axis of moving platform designed as the deviation type can enhance the orientational capability of mechanism. The tilt-and-torsion angle with zero-torsion is used to descript the orientation of moving platform, and the mathematical model is constructed to solve the inverse displacement of the mechanism. On the basis, this study employs local transmission indices (LTI) as the criterion to evaluate the motion/force transmissibility, and analyses the good transmission orientational workspace (GTOW) and good transmission orientational capability (GTOC) of manipulator. This work gives an example of orientational capability analysis and plots the distribution atlases of LTI and GTOW, and the surface of good transmission workspace. Furthermore, the comparison and analysis results indicate that the manipulator with deviation output axis has better performance than one with orthogonal output axis in terms of GTOC, and the GTOC corresponded with the optimal deviation angle can achieve 46°.